Pengaruh Brand Ambassador dan Perilaku Konsumtif Fans NCT Dream terhadap keputusan Pembelian Mie Lemonilo - Dyah Ayu Sekar Dinny; Sugeng Purwanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study discusses the influence of brand ambassadors and consumptive behavior of NCT DREAM’s fans on the purchase decision of Mie Lemonilo. The independent variable in this study is the brand ambassador and consumptive behavior of NCT Dream’s fans while the dependent variable is the purchase decision of Mie Lemonilo. The research method used is a quantitative research method with a total of 100 respondents obtained using a random sampling method from the entire population of NCTzen who are followers of the @JANCITYbase twitter account. This study uses Partial Least Square (PLS) test equipment and the results of this study indicate that brand ambassadors and consumptive behavior have a positive and significant effect on purchasing decisions for Mie Lemonilo.